DISTRIBUTION OF PRIMITIVE ENDODERM AND EPIBLAST LINEAGE SPECIFIC FACTORS IN LATE STAGE BLASTOCYSTS - Duygu Mutluay (Slovenian Veterinary Research, 2016)
Mouse preimplantation development leads to the formation of three distinct cell types by the blastocyst, namely, the trophectoderm (TE) which is an apolarized epihthelial layer, the inner cell mass which forms primitive endoderm, and pluripotent lineage epiblast. Segregation of the lineages is related to the expression of some key factors such as Cdx2, Oct4, Nanog, Gata4 and Sox17. We aimed to understand the role and distribution of these factors in mouse late blastocyst stage embryos. Two cell stage embryos were flushed from mated female B6D2F1 mice 44 hours after human chorionic gonadotropin injection. They were cultured in KSOM-AA medium at 37 °C with 5 % CO2 in humidified air up to the late blastocyst stage. We performed immunofluorescent staining with antibodies specific to these factors. After that blastocysts were imaged and assessed using an fluorescence and confocal laser scanning microscope. We show that lineage specific factors, Gata4 and Sox17, were restricted to primitive endoderm while Nanog was restricted to epiderm lineage at late blastocyst stage. Moreover, the Oct4 protein is present in the nuclei in all cells but is strongly expressed in inner cell mass cells, whereas Cdx2 is localized only in TE cells. We conclude that lineage specific factors, Gata4, Sox17 and Nanog are essential for segregation of distinct lineages and blastocyst development.